2019
DOI: 10.3390/ijms20184489
|View full text |Cite
|
Sign up to set email alerts
|

Avian Expression Patterns and Genomic Mapping Implicate Leptin in Digestion and TNF in Immunity, Suggesting That Their Interacting Adipokine Role Has Been Acquired Only in Mammals

Abstract: In mammals, leptin and tumor-necrosis factor (TNF) are prominent interacting adipokines mediating appetite control and insulin sensitivity. While TNF pleiotropically functions in immune defense and cell survival, leptin is largely confined to signaling energy stores in adipocytes. Knowledge about the function of avian leptin and TNF is limited and they are absent or lowly expressed in adipose, respectively. Employing radiation-hybrid mapping and FISH-TSA, we mapped TNF and its syntenic genes to chicken chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 70 publications
1
26
0
Order By: Relevance
“…In mammals, leptin is a hormone secreted by adipocytes and acts on the hypothalamus to suppress eating and obesity ( Halaas et al, 1995 ). Recently, the leptin gene has been identified in some bird and these findings suggest that avian leptin may have a different physiological function from that of lipid metabolism in mammals ( Seroussi et al, 2017 , 2019 ; Beauclair et al, 2019 ; Friedman-Einat and Seroussi, 2019 ). The present study showed that NPGM is a new player in regulating fat deposition in avian species, chicken.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, leptin is a hormone secreted by adipocytes and acts on the hypothalamus to suppress eating and obesity ( Halaas et al, 1995 ). Recently, the leptin gene has been identified in some bird and these findings suggest that avian leptin may have a different physiological function from that of lipid metabolism in mammals ( Seroussi et al, 2017 , 2019 ; Beauclair et al, 2019 ; Friedman-Einat and Seroussi, 2019 ). The present study showed that NPGM is a new player in regulating fat deposition in avian species, chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic mapping and localization of single-copy gene regions in the genome generally reveal both intra- and interchromosomal rearrangements (i.e., inversions, insertions, deletions or duplications) determined using karyograms [ 9 ]. Moreover, gene loci, which have not yet been mapped within a genome, can be assigned to a specific chromosome within a standardized karyogram [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few disease trials have been conducted to see the response of MHC- Y polymorphisms on Marek’s disease and have reported varied results with no strong impacts but possible influences [ 11 ]. A recent study by Seroussi et al [ 14 ] reported a crucial role of MHC genes in immunity, particularly the avian tumour-necrosis factor (TNF) gene mapped to the MHC- Y region in chicken. Selecting birds with genotypes that are functionally associated with sound immune responses has the potential to control the occurrence of disease in chicken production systems, thus improving correlated production traits [ 9 , 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%